(untitled) (Cadernos de Linguagem e Sociedade, 2010)
The main purpose of this study is to examine the function of ‘involvement’ in journalistic interviews with scientists that object to scientific vulgarization made by the daily press. We have used as our main theoretical foundation the studies by Chafe (1984, 1985). The Jornal do Commercio was chosen as the vehicle-target for this investigation because of its Ciência/Meio Ambiente section, published since 1989, with a specialized staff on environment, science and technology. We used four interviews for the analysis, which have allowed us to identify some characteristics of linguistic behaviour of the participants (scientists and journalists). Our analysis shows that, in this kind of interaction, more than a characteristic trace inherent to verbal interactions, ‘involvement’ is a strategy which aims to guarantee the comprehension of what is uttered.